2022
DOI: 10.1051/0004-6361/202243097
|View full text |Cite
|
Sign up to set email alerts
|

In-depth direct imaging and spectroscopic characterization of the young Solar System analog HD 95086

Abstract: Context. HD 95086 is a young nearby Solar System analog hosting a giant exoplanet orbiting at 57 au from the star between an inner and outer debris belt. The existence of additional planets has been suggested as the mechanism that maintains the broad cavity between the two belts. Aims. We present a dedicated monitoring of HD 95086 with the VLT/SPHERE instrument to refine the orbital and atmospheric properties of HD 95086 b, and to search for additional planets in this system. Methods. SPHERE observations, spre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 107 publications
0
5
0
Order By: Relevance
“…NIRISS Guaranteed Time Observations (GTO) program 1200 will explore the inner architecture of 3 systems with known planets or debris disks, namely HR 8799 (Marois et al 2008(Marois et al , 2010De Rosa et al 2016;Wahhaj et al 2021;Zurlo et al 2022), HD 95086 (Rameau et al 2013a(Rameau et al , 2013b(Rameau et al , 2016Su et al 2015;Desgrange et al 2022) and HD 115600 (Currie et al 2015;Gibbs et al 2019). In all these systems, the structure of the disk or the orbital configuration hint toward the presence of yet undetected companion(s) at short separations.…”
Section: Architecture Of Directly-imaged Extrasolarmentioning
confidence: 99%
“…NIRISS Guaranteed Time Observations (GTO) program 1200 will explore the inner architecture of 3 systems with known planets or debris disks, namely HR 8799 (Marois et al 2008(Marois et al , 2010De Rosa et al 2016;Wahhaj et al 2021;Zurlo et al 2022), HD 95086 (Rameau et al 2013a(Rameau et al , 2013b(Rameau et al , 2016Su et al 2015;Desgrange et al 2022) and HD 115600 (Currie et al 2015;Gibbs et al 2019). In all these systems, the structure of the disk or the orbital configuration hint toward the presence of yet undetected companion(s) at short separations.…”
Section: Architecture Of Directly-imaged Extrasolarmentioning
confidence: 99%
“…Chauvin et al (2018) found that its near-infrared spectral energy distribution is well-fitted by spectral models of dusty and/or young L7-L9 dwarfs. Here, we aim at testing the two scenarios highlighted in Desgrange et al (2022) using SPHERE observations combined with archival observations from VLT/NaCo and Gemini/GPI. These scenarios indicate that the color of the planet can be explained by the presence of a circumplanetary disk around planet b, with a range of high-temperature solutions (1400-1600 K) and significant extinction, or by a super-solar metallicity atmosphere but lower temperatures (800-1300 K), and small to medium amount of extinction.…”
Section: Simulations and Molecular Mapping Analysis Of This Planet Sa...mentioning
confidence: 99%
“…Currently, transit spectroscopy and the direct detection of planetary flux are the most widely used techniques for performing these characterizations. While proven successful for the gaseous giant exoplanets at very short (transiting; e.g., Line et al 2013;Sing et al 2016) or very wide (imaging; e.g., Marois et al 2008;Desgrange, C. et al 2022) orbital distances, Earth-sized exoplanets around Sun-like stars are more challenging and introduce a number of issues. In transit, the smaller planetary sizes and wider orbital distances of habitable terrestrial planets compared to gaseous giant planets mean that they only block a minuscule fraction of their host star upon transiting (e.g., Kaltenegger & Traub 2009;Pallé et al 2011).…”
Section: Introductionmentioning
confidence: 99%